Ahmad Dahlan and the moderate, humanist, and non-sectarian Islam - Mohammad Hasan; Muhammad Taufiq (Penerbit Universiti Kebangsaan Malaysia, 2023)
This article focuses on aspects of moderation, humanism, and non-sectarianism in Ahmad Dahlan’s thoughts and movements (1869–1923 AD) in Islamic education. The method of this article is qualitative with a textual approach and is the result of library research sourced from literature written by Dahlan’s students and scholars of Islamic studies, both classical and contemporary. Based on a moderate understanding extracted from the Quran, hadith, and some scholars’ understanding, Dahlan is more suitable to be categorised as a moderate-humanist or middle Salafism figure rather than being categorised as a puritan-fundamentalist or right-wing Salafism figure as misunderstood by some, because of his thoughts and movements in the Islamic education, religious, social, economic, and political fields are more moderate, nonviolent, open, and visionary humanists than contemporary reformers in the country, so that their thoughts and movements inspire philanthropic actions in the Islamic education, social, economic, and politic fields that are far from radicalism and terrorism, and contrary to the modernist group’s thoughts and movements that exist today, especially with puritan fundamentalist groups.